Perbandingan Risk Dan Return Investasi Pada Emas, Saham Dan Reksadana Dalam Menentukan Keputusan Investasi - Wirawan ED Radianto; Citra Ayuningtyas (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractThe purpose of this study is to investigate whether there are differences in risk and return of investment in investment instruments that investigated the third is gold, LQ 45 index and Mutual Funds. Comparative risk and return is to know where the most profitable instruments so that the right to choose in making investment decisions. The sample used is the price of gold, LQ 45 index and NAV shares of mutual funds during the period from 1997 until 2009. One Way ANOVA is used in this study. The results of this study as follows. There is a significant difference of  risk and return among gold, mutual fund, and LQ 45 index. Finally it can be concluded that gold is the most profitable investment instruments, it is because the smaller the coefficient of variation, the more profitable an investment.